Recurrent Bilateral Chronic Central Serous Chorioretinopathy Treated with Anti-VEGF - Atisundara, Siti Mutia; Iskandar, Erwin (Pusat Mata Nasional Rumah Sakit Mata Cicendo Bandung, 2024)
Introduction: After diabetic retinopathy, branch retinal vein occlusion, and age-related macular degeneration, central serous chorioretinopathy (CSC) is the fourth most frequent retinopathy. Males in their 20s to 50s who have acute or subacute central vision loss or distortion are usually the ones who develop CSC, males more than females. Localized serous macula detachment is its defining feature. Within three to six months, the majority of instances resolve on their own and return to normal vision, but in certain situations, laser or medication treatment may be necessary. Case: A 45-year-old male came with a chief complaint of gradually blurred vision in his right eye since a month ago. Optical computed tomography (OCT) examination showed an accumulation of sub-retinal fluid (SRF) suggestive of CSC. His visual acuity was declining even after being given oral spironolactone for 1 month, so he was scheduled for intravitreal injection Anti-Vascular Endothelial Growth Factor Therapy (Anti-VEGF). After three times in injection right eye the visual acuity improved. One month later he had a chief complaint of gradually blurred vision in his left eye. After three times in injection left eye, CSC in both eyes resolved and the visual acuity improved. Three years later he came back with a chief complaint on both eyes like three years ago. Conclusion: Normally resolution of symptoms from CSC takes several months, treatment with anti- VEGF injection an efficient way to treat CSC resolution time and improve vision.